The Application of Modern Computer-Aided Technology in Fine Art Education. (10th October 2022) - Wang, Baoqi
Abstract : With the popularization of modern computer technology, human society has stepped into the information age. Modern computer technology will have an all-round and deep impact on fine art education in China. In fine art education, various information devices play an important role in broadening the resources of fine art education and effectively improving the quality of fine art education. This study analyzes fine art education in the digital era and studies how the quality of fine art education can be improved through computer-aided technology.